Generational Differences in Workforce and Their Effects on Organizational Performance in Canada - Hamid, Dr.Shahnaz (IJRDO-Journal of Applied Science, 2015)
The paper provides the results of the descriptive research on the generationaldifferences in the workforce of Canada. The aspects of the work with Millennials and itseffects on the organizational performance were studied with the focus on the dataprovided by Statistics Canada and other agencies. It was found that the number ofMillennials, or representatives of Generation Y, in the Canadian labor force is high, andthis fact influences the human resource managers’ practices to improve theorganizational performance. The main positive feature of working with Millennials is theirorientation to innovations and changes. However, Millennials’ focus on flexible workingconditions, high compensation level, and opportunities for the personal and careerdevelopment influence the turnover rates and the organizational performanceaccordingly